2019
DOI: 10.33024/minh.v2i2.2198
|View full text |Cite
|
Sign up to set email alerts
|

Caring behaviors by nurses in patients’ perceptions and experiencing an anxiety during hospitalization

Abstract: Background: Feeling anxious due to lack of attention from the surroundings can be solved by providing a good caring performance from the health workers. The nursing experts place caring as the core principle of a nurse in performing his work. Caring behavior refers to giving attention to patients, respecting others, and showing empathy so that a nurse should maintain the relationship with the patients by having this the patients can commit and be responsible with them.Purpose: Knowing nursing caring behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This finding can be interpreted that the nurses' caring behavior affects the patients' anxiety level who were treated in the isolation room. These results were similar to prior researchs conducted by (Dorman-Ilan et al, 2020) (Xia et al, 2020) (Pribadi & Herwan, 2019) and (Yamamoto-Mitani et al, 2016) which showed a relationship between nurses' caring attitudes when providing nursing care with the anxiety level of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…This finding can be interpreted that the nurses' caring behavior affects the patients' anxiety level who were treated in the isolation room. These results were similar to prior researchs conducted by (Dorman-Ilan et al, 2020) (Xia et al, 2020) (Pribadi & Herwan, 2019) and (Yamamoto-Mitani et al, 2016) which showed a relationship between nurses' caring attitudes when providing nursing care with the anxiety level of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Some of them are self efficacy and work environment. The performance of a nurse can be seen from the quality of nursing care provided to patients (Pujiyanto, Suprihati, Nursalam, & Ediyati, 2017;Hamim, Suwandi, & Yusuf, 2017;Pribadi, & Herwan, 2019). The reference that becomes the basis for measuring the quality of services nursing is the standard of nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, nurses are the most and most often in direct contact with patients. So that the job satisfaction of nurses is also one of the benchmarks that the quality of services nursing has been carried out well (Tagoe, & Quarshie, 2017;Shah, Ali, Dahri, Brohi, Maher, & Hameed, 2018;Pribadi, & Herwan, 2019).…”
Section: Introductionmentioning
confidence: 99%